2013
DOI: 10.3390/proteomes1020159
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Proteomic Approaches to the Elucidation of Potential Biomarkers of Chronic Allograft Injury (CAI)

Abstract: This review focuses on the role of OMICs technologies, concentrating in particular on proteomics, in biomarker discovery in chronic allograft injury (CAI). CAI is the second most prevalent cause of allograft dysfunction and loss in the first decade post-transplantation, after death with functioning graft (DWFG). The term CAI, sometimes referred to as chronic allograft nephropathy (CAN), describes the deterioration of renal allograft function and structure as a result of immunological processes (chronic antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Prior observations suggested that a single biomarker is not likely to reflect the complex pathophysiological process in solid organ transplantation. 31,159 This notion, combined with the advent of a plethora of computational methods, has justified the preference toward the development of proteomic classifiers or protein panels. Additionally, integration of proteomics data with those from other techniques, such as genomics, transcriptomics, and metabolomics, is expected to provide more comprehensive snapshots and a deeper understanding of the mechanisms involved in the pathophysiology after solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior observations suggested that a single biomarker is not likely to reflect the complex pathophysiological process in solid organ transplantation. 31,159 This notion, combined with the advent of a plethora of computational methods, has justified the preference toward the development of proteomic classifiers or protein panels. Additionally, integration of proteomics data with those from other techniques, such as genomics, transcriptomics, and metabolomics, is expected to provide more comprehensive snapshots and a deeper understanding of the mechanisms involved in the pathophysiology after solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first successful kidney transplant in 1954, kidney transplantation has become the routine management for patients presenting with end‐stage renal disease (ESRD) . The two most common causes of long‐term graft loss remain “death with a functioning graft,” usually from a marked excess of cardiovascular mortality in allograft recipients, and chronic allograft nephropathy (CAN) , the term given to the development of fibrotic processes leading to progressive allograft dysfunction with variable proteinuria and hypertension . Despite the significant improvement in the rate of acute rejection over the last decade , CAN remains the principle cause of late graft loss after the first year post renal transplantation , accounting for 50–80% of graft losses after this time .…”
Section: Introductionmentioning
confidence: 99%